(untitled) (Social Science Review, 2026)
Ensuring access to long-acting reversible and permanent contraceptive methods (LARCs & PMs) is essential to 15–49. The BDHS surveys are nationally representative to produce specific indicators at the national and regional levels that use a two-stage stratified sampling method. A multilevel logistic regression analysis was carried out in this study. Using the five cross-sectional waves of the Bangladesh Demographic and Health Surveys (2007 and 2022) this study showed that utilization of LARCs and PMs increased in Bangladesh over the period of time however the rate of improvement is not satisfactory to attain the target of sustainable development goals. The adjusted logistic regression model of this study exhibited that in all four consecutive survey years, there were statistically significant associations between the use of LARCs &PMs and age, number of children, division, education, religion, and family planning service sources. Findings of the study indicates that it is crucial to enhance the government stor’s ability to offer LARCs and PMs, especially by improving public- private partnerships. Current disparities may be addressed through targeted counseling for groups with lower utilization rates and the implementation of incentivization programs. Furthermore, including LARCs and PMs in wider maternal and child health programs could improve access to reproductive healthcare and its outcomes in Bangladesh. Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 101-116